2022
DOI: 10.3390/ijerph19116446
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Subjective Religiosity, Social Support, and Mental Health among Young Students in Eastern Europe during the COVID-19 Pandemic: A Cross-Sectional Study of Poland and Ukraine

Abstract: Religiousness has a positive effect on the mental health of an individual and social groups in many difficult situations. In the conducted research, we wanted to check, inter alia, whether religiosity and social support are positively related to the mental health of students during the COVID-19 pandemic in Poland and Ukraine. The research was conducted at a time (August 2021) when the very contagious Delta variant was spreading over Europe, and numerous pandemic-related personal restrictions and obligations (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…The same study reported that the risk of depressive symptoms and poor sleep quality were, respectively, 63% and 52% lower among individuals who reported higher levels of social support compared with those with low perceived social support 26. In the context of the COVID-19 pandemic, receiving social support was reported to be inversely associated with mental health problems in several countries including China,27 Spain,28 Poland and Ukraine 29…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The same study reported that the risk of depressive symptoms and poor sleep quality were, respectively, 63% and 52% lower among individuals who reported higher levels of social support compared with those with low perceived social support 26. In the context of the COVID-19 pandemic, receiving social support was reported to be inversely associated with mental health problems in several countries including China,27 Spain,28 Poland and Ukraine 29…”
Section: Discussionmentioning
confidence: 92%
“… 26 In the context of the COVID-19 pandemic, receiving social support was reported to be inversely associated with mental health problems in several countries including China, 27 Spain, 28 Poland and Ukraine. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Durante a pandemia da COVID-19, identificou--se a falta de suporte social como o principal fator de risco para transtornos mentais com estudantes jovens (24) . Nesse sentido, quanto maior a autoestima dos adolescentes, melhor será seu comportamento de promoção da saúde, consequentemente, quanto maior o senso de habilidade interpessoal, mais eles serão capazes de implementar o comportamento de apoio social (11) .…”
Section: Discussionunclassified
“…The unprecedented stressors associated with COVID-19, including the illness and death of loved ones, coworkers, and acquaintances, fear of becoming ill or dying from COVID-19, and the unpredictability of the pandemic produced a marked behavioral response that involved religious coping both globally and in the United States (US) [6][7][8][9][10][11][12][13]. In addition, self-isolation and shelter-in-place mandates, the re-arrangement of work environments and schedules, and the shutting down of social and recreational venues also had potentially serious implications for individuals at risk for mental disorders [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%